Targeting AI-2 quorum sensing: harnessing natural products against Streptococcus suis biofilm infection - Shuji Gao; Shuo Yuan; Yingying Quan; Wenjie Jin; Yamin Shen; Rishun Li; Baobao Liu; Yuxin Wang; Li Yi; Shaohui Wang; Xiaogai Hou; Yang Wang (Veterinary Research, 2025)
Abstract The biofilm acts as a protective layer for Streptococcus suis (S. suis), contributing to the development of drug resistance and chronic infections. Autoinducer 2 (AI-2) quorum sensing represents the primary regulatory pathway governing biofilm formation in S. suis. Consequently, targeting AI-2 quorum sensing to inhibit biofilm formation represents a promising strategy for preventing and managing drug resistance and chronic infections caused by S. suis. This study established a small natural product library by integrating commercial drug molecules with Chinese herbal medicine molecules. Consequently, two natural products, salvianolic acid A (SAA) and rhapontin (RH), which target S. suis AI-2 via quorum sensing, were identified. SAA and RH inhibit AI-2 synthesis through noncompetitive and competitive binding to S-ribosylhomocysteinase (LuxS). By inhibiting S. suis AI-2 quorum sensing, these compounds modulate the expression of adhesion genes and the synthesis of extracellular polysaccharides (EPS), reducing the adhesion ability of S. suis and ultimately inhibiting biofilm formation. Using LC‒MS/MS, we further analysed the impact of SAA and RH on the metabolic activity of S. suis, revealing the potential medicinal value of these compounds. Finally, the efficacy of SAA and RH against S. suis infection was validated in Galleria mellonella larvae, confirming their significant anti-infection effects.